Epithelioid Trophoblastic Tumor Around an Abdominal Cesarean Scar: A Pathologic and Molecular Genetic Analysis. (November 2017) - Hsiue, Emily Han-Chung; Hsu, Chiun; Tseng, Li-Hui; Lu, Tzu-Pin; Kuo, Kuan-Ting
Abstract : Epithelioid trophoblastic tumor (ETT) is a rare chemoresistant gestational trophoblastic neoplasm that typically presents as an intrauterine lesion. To our knowledge, no isolated abdominal wall ETT around a Cesarean scar has been reported. Here we describe a 54-yr-old woman with a complex obstetric history who presented with a solitary abdominal wall tumor adjacent to the abdominal Cesarean section scar. The tumor demonstrated typical morphologic and immunophenotypic features of ETT. The gestational origin of the tumor was confirmed by microsatellite genotyping. The tumor enlarged despite the patient undergoing multiagent chemotherapy. Whole-exome sequencing was performed to explore the mechanisms underlying chemoresistance. The ATP-binding cassette subfamily B member 1 ( ABCB1 ) 3435CC genotype, and a putative deleterious x-ray cross-complementing group 4 ( XRCC4 ) Ala73Pro mutations were found. In conclusion, ETT may present as a solitary abdominal wall lesion and microsatellite genotyping could facilitate the determination of its gestational origin. More studies are required to provide mechanistic insights into the chemoresistance of ETT. Abstract : Supplemental Digital Content is available in the text.